PENGARUH POLA ASUH ORANG TUA TERHADAP PRESTASI BELAJAR PESERTA DIDIK KELAS VIIIA PADA MATA PELAJARAN AKIDAH AKHLAK DI MTS RAUDLATUL JANNAH NATAR - Mubarok, Manshur; Sutiono, Sutiono; Sunarto, Sunarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This type of research uses qualitative methods in the form of written or spoken words from people and observable behavior in everyday life. Data collection uses observation, interviews, and documentation methods. Meanwhile, data analysis uses qualitative descriptions, namely through descriptive explanations as conclusions regarding the influence of parenting patterns on student learning achievement (field study at MTs. Raudlatul Jannah Natar). The achievements of these students are inextricably linked to the way parents raise their children. Good parenting styles positively impact both a child's behavior and achievement. Therefore, parenting styles significantly influence a child's intelligence and academic performance. Appropriate parenting styles enhance and develop a child's potential, leading to positive achievement. Keywords: The Influence of Parenting Styles